Improvement of teacher’s professional competency in strengthening learning methods to maximize curriculum implementation - Hendro Prasetyono; Agus Abdillah; Tjipto Djuhartono; Ira Pratiwi Ramdayana; Laila Desnaranti (Institute of Advanced Engineering and Science, 2021)
The 2013 curriculum which has been implemented for more than six years in Indonesia has many problems in its application. Therefore, we need to conduct empirical research to determine the causes of the ineffective implementation of the 2013 curriculum in schools. This study involved 13 high schools and vocational high schools in the provinces of DKI Jakarta and West Java with a total of 420 students, 26 teachers, and principals as respondents. The research employed mixed parallel method and data analysis using combined analysis of qualitative and quantitative approaches. The research found that there are still schools that use two different curricula, 2013 curriculum and school-based curriculum. In implementing the 2013 curriculum, teachers are required to use various learning with a scientific approach that refers to student-centered concepts. There is a need for the training program to improve teachers’ professional competence, especially in the terms of various learning methods mastery.